The Effect of Service Quality, Promotion, and Price on Customer Satisfaction in Pt. Pos Indonesia (Persero) Pati - Dhea Romadhona Achmadi; Sarwani Sarwani; Dian Ferriswara; Damajanti Sri Lestari (LPPM STIE Kasih Bangsa, 2026)
PT Pos Indonesia (Persero), as a long-established Indonesian state-owned enterprise, faces increasing competitive pressure in the logistics industry due to the rapid growth of e-commerce and the emergence of digital-based private courier services. This study focuses on the Pati Branch Post Office, which has experienced rising delivery demand while continuing to encounter challenges related to service quality, promotional effectiveness, and customer price perceptions—factors that potentially influence customer satisfaction. The study aims to analyze the partial and simultaneous effects of service quality, promotion, and pricing on customer satisfaction at the Pati Branch Post Office. A quantitative research approach was employed using survey data collected through questionnaires distributed to customers. The data were analyzed using multiple linear regression to examine the relationships among variables. The results indicate that service quality is the most dominant factor influencing customer satisfaction. Promotion and pricing also have a statistically significant effect, although their influence is relatively weaker compared to service quality. These findings highlight the importance for PT Pos Indonesia to prioritize improvements in service reliability, responsiveness, and assurance to enhance the overall customer experience. In addition, strengthening digital-based promotional strategies and implementing value-based pricing are shown to positively shape customer perceptions. Overall, this study concludes that improving customer satisfaction at the Pati Branch Post Office is primarily driven by service quality enhancement, supported by effective promotion and appropriate pricing strategies aligned with customer value expectations.